A method for testing the liquid retention rate of a lithium battery separator
Patent Information
- Application Number
- CN202611138811.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
一种锂电池隔膜储液率测试方法,包括检测袋、压板组件和抽真空组件,所述测试方法包括以下步骤:S1:称量检测袋重量M0,将电解液加入检测袋内,使电解液与检测袋内壁充分接触,通过压板组件按第一预设压力夹持检测袋,并通过抽真空组件按第一预设时长对检测袋进行抽真空,将电解液从检测袋中抽出,称取得到检测袋重量M1,检测袋中的电解液留存重量Mk=M1-M0;S2:裁切出预设尺寸的隔膜样品,称取隔膜样品重量M3,将隔膜样品放入检测袋中,将电解液加入检测袋内直至完全淹没隔膜样品,通过电解液将隔膜样品浸润至饱和状态,制得检测样品;S3:通过压板组件按第二预设压力对检测样品进行夹持,并通过抽真空组件按第二预设时长对检测样品进行抽真空,将检测样品内多余的电解液抽出,称取检测样品重量M4;所述第一预设压力和第二预设压力相同,所述第一预设时长和第二预设时长相同;S4:所述隔膜样品储液率W=(M4-M0-M3-Mk)/M3*100%;通过设置检测袋、压板组件和抽真空组件,在检测时无需使隔膜样品暴露在环境中,并且不需要手动擦除隔膜表面电解液,在检测时计算并减去检测袋的电解液留存重量,解决检测效率和检测精度低的问题
通过设置检测袋、压板组件和抽真空组件,在检测时隔膜放置在检测袋内,无需使隔膜样品暴露在环境中,降低环境因素的影响,通过压板组件和抽真空组件去除多余电解液,不需要手动擦除隔膜表面电解液,提高检测精确度和检测效率;
Smart Images

Figure CN122982831A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery separator technology, and more specifically to a method for testing the liquid storage capacity of lithium battery separators. Background Technology
[0002] Lithium-ion batteries, characterized by high energy density, low self-discharge, and long cycle life, are widely used in various electronic devices and electric vehicles. As a key component of lithium-ion batteries, the separator has a crucial impact on battery performance and safety. The separator not only separates the positive and negative electrodes to prevent short circuits, but also adsorbs electrolyte to ensure high ionic conductivity, while preventing the migration of harmful substances and improving battery safety.
[0003] Currently, the main method for testing the electrolyte retention rate of lithium battery separators is the immersion solvent weighing method. After weighing the separator, the weight M1 is recorded. The separator is placed in a container and immersed in electrolyte to absorb the electrolyte. After being removed, the electrolyte on the surface of the separator is wiped off with lint-free paper, and the weight M2 is recorded. The absorption rate is calculated by measuring the weight difference per unit volume of the separator before and after electrolyte absorption. However, the traditional immersion solvent weighing method is easily affected by human factors after wiping off the surface electrolyte of the separator after immersion. In addition, during the testing process, the separator is exposed to the external environment, resulting in poor consistency of the test data and low testing accuracy. Summary of the Invention
[0004] This invention addresses the shortcomings of existing technologies by providing a method for testing the liquid storage rate of lithium battery separators. This method can reduce the influence of human and environmental factors during separator liquid storage rate testing and improve the accuracy of separator liquid storage rate testing.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A method for testing the electrolyte retention rate of a lithium battery separator includes a test bag, a pressure plate assembly, and a vacuum assembly. The test method includes the following steps: S1: Weigh the test bag (M0), add electrolyte into the test bag to ensure full contact between the electrolyte and the inner wall of the test bag, clamp the test bag with the pressure plate assembly at a first preset pressure, and vacuum the test bag for a first preset time using the vacuum assembly to extract the electrolyte from the test bag. Weigh the test bag (M1), and the remaining electrolyte weight in the test bag is Mk = M1 - M0; S2: Cut a separator sample of a preset size, weigh the separator sample (M3), place the separator sample into the test bag, and add electrolyte into the test bag until the separator sample is completely submerged, saturating the separator sample with the electrolyte. S3: The test sample is clamped by the pressure plate assembly at a second preset pressure, and the test sample is evacuated by the vacuum assembly for a second preset time to extract the excess electrolyte in the test sample, and the weight of the test sample M4 is weighed; the first preset pressure and the second preset pressure are the same, and the first preset time and the second preset time are the same; S4: the liquid storage rate of the diaphragm sample W = (M4-M0-M3-Mk) / M3*100%; by setting up the test bag, the pressure plate assembly and the vacuum assembly, the diaphragm sample does not need to be exposed to the environment during the test, and it does not need to be manually wiped off the electrolyte on the surface of the diaphragm. The weight of the electrolyte remaining in the test bag is calculated and subtracted during the test, which solves the problems of low detection efficiency and low detection accuracy.
[0006] As a preferred embodiment, both the first preset pressure and the second preset pressure are 30-80 kPa.
[0007] As a preferred embodiment, both the first preset duration and the second preset duration are 45-85 seconds.
[0008] As a preferred embodiment, in step S1, M1 is the maximum weight of the detection bag obtained by repeatedly adding electrolyte to the detection bag and then extracting it.
[0009] As a preferred embodiment, in step S1, the electrolyte retention weight Mk is the average electrolyte retention weight calculated by repeating step S1 more than twice.
[0010] As a preferred embodiment, in step S2, the diaphragm sample is immersed in the electrolyte for 15-45 minutes.
[0011] As a preferred embodiment, in step 2, the diaphragm sample is impregnated at room temperature (23-25°C).
[0012] As a preferred embodiment, the testing bag is any one of the following: polytetrafluoroethylene film bag, aluminum-plastic composite film bag, polyvinylidene fluoride film bag, polyethylene composite bag, polypropylene composite bag, and modified PET composite material bag.
[0013] As a preferred embodiment, the pressure plate assembly includes a first pressure plate, a second pressure plate, a pressure sensor, and a driving device. Both the first and second pressure plates are driven and connected to the driving device. The pressure sensor is used to detect the clamping pressure at the clamping position. A clamping position is formed between the first and second pressure plates. During operation, the driving device drives the first and second pressure plates to move closer to or further away from each other.
[0014] As a preferred embodiment, the vacuuming assembly includes a collection container for collecting the electrolyte extracted by the vacuuming assembly.
[0015] Compared with the prior art, the present invention has significant advantages and beneficial effects, specifically, By setting up a detection bag, pressure plate assembly, and vacuum assembly, the diaphragm is placed inside the detection bag during detection, eliminating the need to expose the diaphragm sample to the environment and reducing the influence of environmental factors. The pressure plate assembly and vacuum assembly remove excess electrolyte, eliminating the need to manually wipe the electrolyte off the diaphragm surface, thus improving detection accuracy and efficiency. The accuracy of detection is further improved by calculating and subtracting the weight of the electrolyte remaining in the detection bag during the detection process.
[0016] To more clearly illustrate the structural features, technical means, and specific objectives and functions achieved by the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments: Attached Figure Description
[0017] Figure 1 This is a process flow diagram of an embodiment of the present invention; Figure 2 This is a schematic diagram of the structure of the detection bag, pressure plate assembly, and vacuum assembly according to an embodiment of the present invention.
[0018] Explanation of reference numerals in the attached diagram: 10. Testing bags; 20. Pressure plate assembly; 21. First pressure plate; 22. Second pressure plate; 23. Pressure sensor; 24. Drive device; 25. Clamping position; 30. Vacuum pumping assembly; 40. Diaphragm sample. Detailed Implementation
[0019] In the description of this invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the indicated position or element must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0020] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0021] like Figure 1-2 As shown, this invention discloses a method for detecting the electrolyte storage rate of a lithium battery separator, including a test bag 10, a pressure plate assembly 20, and a vacuum assembly 30. The detection method includes the following steps: S1: Weighing the test bag 10 by weight M0, adding electrolyte into the test bag 10 to ensure full contact between the electrolyte and the inner wall of the test bag 10, clamping the test bag 10 with a first preset pressure using the pressure plate assembly 20, and vacuuming the test bag 10 for a first preset time using the vacuum assembly 30 to extract the electrolyte from the test bag 10, weighing the test bag 10 by weight M1, and determining the remaining electrolyte weight in the test bag 10 as Mk = M1 - M0; S2: Cutting out a separator sample 40 of a preset size, weighing the separator sample 40 by weight M3, placing the separator sample 40 into the test bag 10, adding electrolyte into the test bag 10 until the separator sample 40 is completely submerged, and then... The electrolyte is used to saturate the diaphragm sample 40 to obtain the test sample; S3: The test sample is clamped by the pressure plate assembly 20 at a second preset pressure, and the test sample is evacuated by the vacuum assembly 30 for a second preset time to extract the excess electrolyte in the test sample, and the weight of the test sample M4 is weighed; The first preset pressure and the second preset pressure are the same, and the first preset time and the second preset time are the same; S4: The liquid storage rate of the diaphragm sample 40 is W = (M4 - M0 - M3 - Mk) / M3 * 100%; By setting the test bag 10, the pressure plate assembly 20 and the vacuum assembly 30, the diaphragm sample 40 does not need to be exposed to the environment during the test, and the electrolyte on the diaphragm surface does not need to be manually wiped off. The weight of the electrolyte remaining in the test bag 10 is calculated and subtracted during the test, which solves the problems of low detection efficiency and low detection accuracy.
[0022] In this invention, the vacuum pumping component 30 is a vacuum pump with a vacuuming capacity of 95-100 kPa and a vacuum degree of 99.9%. The structure and technical principle of the vacuum pump are existing technologies and will not be described in detail here.
[0023] It should be understood that in step S3, under the action of pressure and vacuum, the excess electrolyte inside the bag and on the surface of the diaphragm is extracted by compressing the space inside the detection bag 10. The detection bag 10 has a certain degree of support and cannot compress the pores of the diaphragm sample, thus preserving the electrolyte inside the pores of the diaphragm sample to the greatest extent and ensuring the accuracy of the detection data.
[0024] In this invention, the electrolyte is a mature product that can be purchased directly from the market, which is existing technology and will not be described in detail here.
[0025] The first preset pressure and the second preset pressure are both 30-80 kPa; preferably 50 kPa.
[0026] The first preset duration and the second preset duration are both 45-85s; preferably 60s.
[0027] In step S1, M1 is the maximum weight of the detection bag 10 obtained by repeatedly adding electrolyte to the detection bag 10 and then extracting it.
[0028] In step S1, the electrolyte retention weight Mk is the average electrolyte retention weight calculated by repeating step S1 two or more times.
[0029] In step S2, the membrane sample 40 is immersed in the electrolyte for 15-45 minutes; preferably 30 minutes.
[0030] In step S2, the diaphragm sample 40 is immersed at room temperature (23-25°C); preferably at 25°C.
[0031] The testing bag 10 is any one of polytetrafluoroethylene film bag, aluminum-plastic composite film bag, polyvinylidene fluoride film bag, polyethylene composite bag, polypropylene composite bag, and modified PET composite material bag; preferably, it is a polytetrafluoroethylene film bag.
[0032] The pressure plate assembly 20 includes a first pressure plate 21, a second pressure plate 22, a pressure sensor 23, and a driving device 24. Both the first pressure plate 21 and the second pressure plate 22 are driven and connected to the driving device 24. A clamping position 25 is formed between the first pressure plate 21 and the second pressure plate 22. The pressure sensor 23 is used to detect the clamping pressure of the clamping position 25. During operation, the driving device 24 drives the first pressure plate 21 and the second pressure plate 22 to move closer to or further away from each other. The above configuration makes the pressure plate assembly 20 easy to operate and carry, and convenient to use. The pressure sensor 23 enables real-time monitoring of pressure changes, precise control, and improved detection accuracy.
[0033] In this invention, the structure and technical principle of the pressure sensor 23 are existing technologies and will not be described in detail here.
[0034] In this invention, the driving device 24 is a combination of a motor and a lead screw, a hydraulic cylinder, or a stepper motor.
[0035] The vacuum assembly 30 includes a collection container (not shown in the figure) for collecting the electrolyte extracted by the vacuum assembly 30; the collection container can prevent electrolyte overflow and leakage.
[0036] In summary, this invention, by setting up a detection bag 10, a pressure plate assembly 20, and a vacuum assembly 30, allows the diaphragm sample 40 to be placed inside the detection bag 10 during testing, eliminating the need for the diaphragm sample 40 to be exposed to the environment and reducing the influence of environmental factors. The pressure plate assembly 20 and the vacuum assembly 30 remove excess electrolyte, eliminating the need for manual wiping of the electrolyte from the diaphragm surface, thus improving detection accuracy and efficiency. Furthermore, by calculating and subtracting the weight of the electrolyte remaining in the detection bag 10 during testing, detection accuracy is further improved.
[0037] The above-described solution will be further illustrated below with reference to specific embodiments and comparative examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.
[0038] In this invention, the coefficient of variation (CV) is a key indicator for measuring the accuracy of the detection data. The smaller the deviation between the detected data and the lower the CV value, the better the consistency of the repeated detection results and the more accurate the results. Conversely, the larger the deviation between the detected data and the higher the CV value, the worse the consistency of the repeated detection results and the less accurate the results.
[0039] Average storage rate The formula for calculating the coefficient of variation (CV) is as follows: Average storage rate =W1+W2+W3+....+Wn / n; Coefficient of variation (CV) = Standard deviation / *100%.
[0040] Example 1
[0041] Step 1: Weigh the test bag 10 by weight M0, add electrolyte into the test bag 10 to ensure full contact between the electrolyte and the inner wall of the test bag 10, clamp the test bag 10 with the pressure plate assembly 20 at a first preset pressure of 30 kPa, and vacuum the test bag 10 with the vacuum assembly 30 for a first preset time of 45 s to extract the electrolyte from the test bag 10. Weigh the test bag 10 by weight M1, and the electrolyte weight remaining in the test bag 10 is Mk = M1 - M0. Repeat the above operation 10 times to obtain the average electrolyte weight remaining Mk. Step 2: Cut out a 70mm*70mm diaphragm sample 40, weigh the diaphragm sample 40 by weight M3, put the diaphragm sample 40 into the test bag 10, add electrolyte into the test bag 10 until the diaphragm sample 40 is completely submerged, immerse at 23℃ for 15 minutes, and immerse the diaphragm sample 40 to saturation through the electrolyte to obtain the test sample. Step 3: The test sample is clamped by the pressure plate assembly 20 at a second preset pressure of 30 kPa, and the test sample is evacuated by the vacuum assembly 30 for a second preset duration of 45 s to remove excess electrolyte from the test sample. The weight of the test sample M4 is then measured. Step 4: The liquid storage rate of the diaphragm sample 40 is W = (M4 - M0 - M3 - Mk) / M3 * 100%.
[0042] Three types of diaphragm samples were selected: a single-layer PE microporous membrane, a three-layer PE composite membrane, and a ceramic-coated PE membrane. Ten samples of each type were taken and tested according to the above steps. The average liquid storage capacity of each diaphragm sample in Example 1 was then calculated. and coefficient of variation (CV);
[0043] Example 2
[0044] Step 1: Weigh the test bag 10 by weight M0, add electrolyte into the test bag 10 to ensure full contact between the electrolyte and the inner wall of the test bag 10, clamp the test bag 10 with the pressure plate assembly 20 at a first preset pressure of 50 kPa, and vacuum the test bag 10 with the vacuum assembly 30 for a first preset time of 60 s to extract the electrolyte from the test bag 10. Weigh the test bag 10 by weight M1, and the electrolyte weight remaining in the test bag 10 is Mk = M1 - M0. Repeat the above operation 10 times to obtain the average electrolyte weight remaining Mk. Step 2: Cut out a 70mm*70mm diaphragm sample 40, weigh the diaphragm sample 40 by weight M3, put the diaphragm sample 40 into the test bag 10, add electrolyte into the test bag 10 until the diaphragm sample 40 is completely submerged, immerse at 24℃ for 30 minutes, and immerse the diaphragm sample 40 to saturation through the electrolyte to obtain the test sample. Step 3: The test sample is clamped by the pressure plate assembly 20 at a second preset pressure of 50 kPa, and the test sample is evacuated by the vacuum assembly 30 for a second preset duration of 60 s to remove excess electrolyte from the test sample. The weight of the test sample M4 is then measured. Step 4: The liquid storage rate of the diaphragm sample 40 is W = (M4 - M0 - M3 - Mk) / M3 * 100%.
[0045] Three types of diaphragm samples were taken: a single-layer PE microporous membrane, a three-layer PE composite membrane, and a ceramic-coated PE membrane. Ten samples of each type were taken and tested according to the above steps. The average liquid storage capacity of each type of diaphragm sample in Example 2 was then calculated. and coefficient of variation (CV);
[0046] Example 3
[0047] Step 1: Weigh the test bag 10 by weight M0, add electrolyte into the test bag 10 to ensure full contact between the electrolyte and the inner wall of the test bag 10, clamp the test bag 10 with the pressure plate assembly 20 at a first preset pressure of 80 kPa, and vacuum the test bag 10 with the vacuum assembly 30 for a first preset time of 85 s to extract the electrolyte from the test bag 10. Weigh the test bag 10 by weight M1, and the electrolyte weight remaining in the test bag 10 is Mk = M1 - M0. Repeat the above operation 10 times to obtain the average electrolyte weight remaining Mk. Step 2: Cut out a 70mm*70mm diaphragm sample 40, weigh the diaphragm sample 40 by weight M3, put the diaphragm sample 40 into the test bag 10, add electrolyte into the test bag 10 until the diaphragm sample 40 is completely submerged, immerse at 25℃ for 45min, and immerse the diaphragm sample 40 to saturation through the electrolyte to obtain the test sample. Step 3: The test sample is clamped by the pressure plate assembly 20 at a second preset pressure of 80 kPa, and the test sample is evacuated by the vacuum assembly 30 for a second preset duration of 85 s to remove excess electrolyte from the test sample. The weight of the test sample M4 is then measured. Step 4: The liquid storage rate of the diaphragm sample 40 is W = (M4 - M0 - M3 - Mk) / M3 * 100%.
[0048] Three types of diaphragm samples were taken: a single-layer PE microporous membrane, a three-layer PE composite membrane, and a ceramic-coated PE membrane. Ten samples of each type were taken and tested according to the above steps. The average liquid storage capacity of each type of diaphragm sample in Example 3 was then calculated. and coefficient of variation (CV); Comparative Example 1 Comparative Example 1 uses the traditional soaking and weighing method, and the specific operating steps are as follows: Step 1: Cut out a 70mm*70mm diaphragm sample 40, weigh the diaphragm sample 40 by weight M5, and put the diaphragm sample 40 into the electrolyte and soak it at room temperature (25℃) for 30 minutes. Step 2: Use tweezers to remove the diaphragm sample 40 and after 5 seconds of draining, gently wipe both sides of the diaphragm sample 40 once with a lint-free paper. Weigh the diaphragm sample 40 by weight M6. Step 3, the liquid storage rate of the diaphragm sample 40 is W = (M6 - M5) / M5 * 100%; Three types of diaphragm samples were selected: PE single-layer microporous membrane, PE three-layer composite membrane, and ceramic-coated PE membrane. Ten samples of each type were taken and tested according to the above steps. The average liquid storage capacity of each diaphragm sample in Comparative Example 1 was then calculated. and coefficient of variation (CV); Comparative Example 2 Step 1: Weigh the test bag 10 by weight M7, cut out a 70mm*70mm diaphragm sample 40, weigh the diaphragm sample 40 by weight M8, put the diaphragm sample 40 into the test bag 10, add electrolyte into the test bag 10 until the diaphragm sample 40 is completely submerged, soak at 24℃ for 30 minutes, and soak the diaphragm sample 40 to saturation through the electrolyte to obtain the test sample; Step 3: The test sample is clamped by the pressure plate assembly 20 with a clamping pressure of 50 kPa, and the test sample is evacuated by the vacuum assembly 30 for 60 seconds to remove excess electrolyte from the test sample. The weight of the test sample M9 is then measured. Step 4: The liquid storage rate of the diaphragm sample 40 is W = (M9-M7-M8) / M8*100%.
[0049] Three types of diaphragm samples were selected: PE single-layer microporous membrane, PE three-layer composite membrane, and ceramic-coated PE membrane. Ten samples of each type were taken and tested according to the above steps. The average liquid storage capacity of each diaphragm sample in Comparative Example 2 was then calculated. and coefficient of variation (CV); In this invention, the vacuum levels of the evacuation in Examples 1-3 and Comparative Example 1 are all the same.
[0050] The thickness and porosity of the three membrane samples 40 are shown in Table 1: Table 1 Average storage capacity of Examples 1-3 and Comparative Examples 1-2 The coefficient of variation (CV) is shown in Table 2:
[0051] Table 2 From Table 2, we can see that: Comparing the data from Examples 1-3, Example 3 had the highest clamping pressure, the longest vacuuming time, and the electrolyte adhering to the diaphragm surface could be removed more thoroughly. The measured liquid storage rate was more accurate, and the CV value was the lowest. The test results showed high consistency and the test accuracy was the highest. Comparing Examples 1-3 with Comparative Example 1, since Comparative Example 1 used lint-free paper to wipe the surface of the diaphragm sample 40 to remove excess electrolyte, there were individual differences in the force, angle and dwell time of the lint-free paper wiping operation, resulting in significantly higher CV values for the three diaphragm samples in Comparative Example 1, all of which were greater than 8.7%, far exceeding the CV values of Examples 1-3. The consistency of the detection results was poor and the detection accuracy was low.
[0052] Example 2 is compared with Comparative Example 2. The difference between Example 2 and Comparative Example 2 is that Comparative Example 2 did not calculate and subtract the weight of the electrolyte remaining in the detection bag 10. From the results of the average liquid storage rate test, it can be seen that since the weight of the electrolyte remaining in the test bag 10 was not subtracted, the average liquid storage rate of the three diaphragm samples 40 in Comparative Example 2 was greater than that of the three diaphragm samples 40 in Example 2. This indicates that the weight of the electrolyte remaining in the test bag 10 will reduce the accuracy of the liquid storage rate test of the diaphragm sample 40. It can be seen that by calculating and subtracting the weight of the electrolyte remaining in the test bag 10, the error can be effectively eliminated and the test can be made more accurate. From the CV value, since the weight of electrolyte remaining in the test bag 10 was not calculated and subtracted, and the weight of electrolyte remaining in each test bag 10 is different, the CV values of the three diaphragm samples 40 in Comparative Example 2 are all greater than the CV values of the three diaphragm samples 40 in Example 2. This further illustrates that the weight of electrolyte remaining in the test bag 10 will reduce the accuracy of the liquid storage rate detection of diaphragm sample 40.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the actual technology of the present invention shall still fall within the scope of the technical solution of the present invention.
Claims
1. A method for testing the liquid storage capacity of a lithium battery separator, characterized in that: The test method includes a test bag, a pressure plate assembly, and a vacuum assembly, and comprises the following steps: S1: Weigh the test bag M0, add electrolyte into the test bag to make full contact between the electrolyte and the inner wall of the test bag, clamp the test bag with the pressure plate assembly at the first preset pressure, and vacuum the test bag with the vacuum assembly for the first preset time to extract the electrolyte from the test bag, weigh the test bag M1, and the remaining weight of the electrolyte in the test bag Mk=M1-M0; S2: Cut out a diaphragm sample of the preset size, weigh the diaphragm sample M3, put the diaphragm sample into the test bag, add electrolyte into the test bag until the diaphragm sample is completely submerged, and wet the diaphragm sample to saturation through the electrolyte to obtain the test sample. S3: The test sample is clamped by the pressure plate assembly at the second preset pressure, and the test sample is evacuated by the vacuum assembly for the second preset duration to extract the excess electrolyte in the test sample, and the weight of the test sample M4 is weighed; the first preset pressure and the second preset pressure are the same, and the first preset duration and the second preset duration are the same. S4: The liquid storage rate of the diaphragm sample is W = (M4 - M0 - M3 - Mk) / M3 * 100%.
2. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, The first preset pressure and the second preset pressure are both 30-80 kPa.
3. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, The first preset duration and the second preset duration are both 45-85s.
4. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, In step S1, M1 is the maximum weight of the detection bag obtained by repeatedly adding electrolyte to the detection bag and then extracting it.
5. The method for testing the liquid storage capacity of a lithium battery separator according to claim 4, characterized in that, In step S1, the electrolyte retention weight Mk is the average electrolyte retention weight calculated by repeating step S1 two or more times.
6. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, In step S2, the membrane sample is immersed in the electrolyte for 15-45 minutes.
7. The method for testing the liquid storage capacity of a lithium battery separator according to claim 6, characterized in that, In step 2, the diaphragm sample is immersed at room temperature (23-25°C).
8. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, The testing bag is any one of the following: polytetrafluoroethylene film bag, aluminum-plastic composite film bag, polyvinylidene fluoride film bag, polyethylene composite bag, polypropylene composite bag, and modified PET composite material bag.
9. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, The pressure plate assembly includes a first pressure plate, a second pressure plate, a pressure sensor, and a driving device. Both the first and second pressure plates are driven and connected to the driving device. The pressure sensor is used to detect the clamping pressure at the clamping position. A clamping position is formed between the first and second pressure plates. During operation, the driving device drives the first and second pressure plates to move closer to or further away from each other.
10. The method for testing the liquid storage capacity of a lithium battery separator according to claim 1, characterized in that, The vacuuming assembly includes a collection container for collecting the electrolyte extracted by the vacuuming assembly.